If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -97)(x + -3) = 0 Reorder the terms: (-97 + x)(x + -3) = 0 Reorder the terms: (-97 + x)(-3 + x) = 0 Multiply (-97 + x) * (-3 + x) (-97(-3 + x) + x(-3 + x)) = 0 ((-3 * -97 + x * -97) + x(-3 + x)) = 0 ((291 + -97x) + x(-3 + x)) = 0 (291 + -97x + (-3 * x + x * x)) = 0 (291 + -97x + (-3x + x2)) = 0 Combine like terms: -97x + -3x = -100x (291 + -100x + x2) = 0 Solving 291 + -100x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (3 + -1x)(97 + -1x) = 0Subproblem 1
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Subproblem 2
Set the factor '(97 + -1x)' equal to zero and attempt to solve: Simplifying 97 + -1x = 0 Solving 97 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-97' to each side of the equation. 97 + -97 + -1x = 0 + -97 Combine like terms: 97 + -97 = 0 0 + -1x = 0 + -97 -1x = 0 + -97 Combine like terms: 0 + -97 = -97 -1x = -97 Divide each side by '-1'. x = 97 Simplifying x = 97Solution
x = {3, 97}
| x^3-30x+3=0 | | 5a+7b=57 | | 5d-7=13 | | 72.1y= | | 4/9-(7/9-2/9) | | 1/5×10.5 | | 1/7×10.5 | | a^3-6b^2+59c=6 | | 21x^2-12x=-1 | | f(x+7)=x^2+8x+45 | | 9+6x=36 | | 6+5x=456 | | 2senx(cos^2x)-senx=0 | | 2cos^2-5cosx+2=0 | | 3senx+cosx-3=o | | x+2y=123 | | 3senx+cosx-3=0 | | 6(4-x)+55=5(2+3x) | | 26x^2-130x-104=0 | | 5-3x+1=-3 | | x/10-3=7 | | 153.48=2.26w+15.68 | | logy=1.9 | | 5-3x+1=4x-3 | | 19.5=2.26w+15.86 | | 10x+2y*2y=100 | | 2timesy=3.6 | | .5+2.5y=2.6+0.4y | | x+y-62=-27 | | 10(3x+19)=70 | | 7(3s+3)=252 | | (-5/28Z^7)(7/20z^2) |